Childhood Infections and Subsequent School Achievement Among 598, 553 Danish Children. Issue 8 (August 2018) - Köhler-Forsberg, Ole; Sørensen, Holger J.; Nordentoft, Merete; McGrath, John J.; Benros, Michael E.; Petersen, Liselotte
Abstract : Background: Hospitalizations for infections have been associated with subsequent decreased cognitive ability, but it is uncertain if childhood infections influence subsequent scholastic achievement (SA). We aimed to estimate the association between infections during childhood and SA. Methods: Nationwide prospective cohort study including 598, 553 children born in Denmark between 1987 and 1997 and their parents. Exposures were hospitalization for infections and treatment with anti-infective agents. Outcomes were completion of ninth grade and ninth grade test scores. Data were analyzed with logistic and linear regression analysis techniques and adjusted for any mental disorder, birthweight, Apgar score, malformations at birth, chronic somatic diseases, first-born child, parental educational level and parental mental disorders. Results: Hospitalization with infections was linked to lower completion of ninth grade with an odds ratio of 0.82 (95% confidence interval: 0.79–0.85) compared with children without prior hospitalizations for infections. Dose–response relationships were observed with respect to number of hospital contacts for infections and a shorter time since last hospitalization (all P < 0.001). Among those who completed the ninth grade test score, we found a dose–response and time–since relationship between number of prior severe infections and subsequent lower grade scores ( P < 0.001). Treatment of nonsevere infections with anti-infective agents did not predict lower completion of ninth grade but was associated with lower grade scores ( P < 0.001). Conclusions: Infections, particularly those requiring hospitalizations, were associated with subsequent affected cognitive ability as indicated by lower SA. These findings might also be explained by missed school days or socioeconomic factors associated with the susceptibility of acquiring infections. Abstract : Supplemental Digital Content is available in the text.